ACL injury timing during matches in professional women's football: A 208-case analysis from the 2022-2024 seasons - Hampstead, W.; Crespin, V.; Wakefield, B.; Whalan, M.; Lovell, R.; Pappas, E. (Journal of Science and Medicine in Sport, 2025)
Objectives This study aimed to analyse the timing of ACL injuries during match play in professional women's football games.